Health Education on the Dangers of Excessive Sugar Consumption for Students of Istiqamah Muhammadiyah Islamic Boarding School in Samarinda East Kalimantan Using Leaflet Media: Penyuluhan Bahaya Konsumsi Gula Berlebih Bagi Kesehatan pada Siswa/Siswi Pesantren Istiqamah Muhammadiyah Samarinda Kalimantan Timur dengan Media Leaflet - Fitriani, Nurul; Kilab, Ridha Yulia Fajriani; Morri, Farah Syifa Eka; Akbar, Muhammad (B-Creta Publisher, 2025)
In recent decades, the consumption of sugary foods and beverages has significantly increased in various parts of the world, including Indonesia. School-aged children tend to develop habits of purchasing and consuming unhealthy foods, both within the school environment and in their surrounding neighborhoods. Therefore, efforts are needed to limit excessive sugar consumption for the sake of health. One such effort has been carried out at Pesantren Istiqamah Muhammadiyah. This health promotion activity aimed to raise participants' awareness about the dangers of excessive sugar intake. The educational activity was conducted through the distribution of leaflets and a presentation using PowerPoint slides. The results showed that 20 participants attended the session. Initially, they had limited understanding of the health risks associated with high sugar consumption, but their understanding improved after the session. This was reflected in the pre-test results, where only 14 participants fell into the “good” understanding category, whereas the post-test results showed an increase to 18 participants in that category. In other words, the session successfully improved participants' knowledge about the negative impacts of excessive sugar consumption on health, including the risks of obesity, diabetes mellitus, heart disease, kidney disease, and tooth decay.